The responses of stress tolerance, physiological performance and energy metabolism to acclimation temperature between tropical and temperate fish species - Yong-Fei Zhang; Ping Xiang; Shi-Jian Fu (Frontiers in Marine Science)
The responses of stress tolerance and other critical physiological functions of fish species to temperature fluctuations, and the potential relationships with their thermal history and natural habitat conditions, are vital for future population dynamic and distribution. In the present study, the thermal and hypoxia tolerance capacities, oxygen uptake capacity, swimming capacity and energy metabolism traits of two tropical and two temperate fish species acclimated at three temperatures were measured. Two tropical species exhibited much poorer cold tolerance than temperate species as expected. However, irrespective of thermal history, the two species preferred small and stagnant waterbody habitats exhibited greater heat tolerance capacity, lower swimming capacity, higher oxygen supply capacity. hence, higher hypoxia tolerance than the two species preferred to open waterbody. As anticipated, thermal tolerance capacity changed in parallel with acclimation temperature. However, hypoxia tolerance appeared to be the least sensitive to the acclimation temperature, suggesting it is the vital and conservative physiological function for aquatic breathe animals. One of the underlying mechanisms is the parallel increase in oxygen supply capacity with the increased energy and oxygen demanding by higher acclimation temperatures. All variables involved swimming capacity and metabolic parameters were more sensitive in the two tropical species, whereas one eury-thermal species was the least sensitive to temperature change. Moreover, the present study also suggests that in some species, maximum metabolic rate elicited by locomotion and digestion might exhibit different temperature sensitivity ranges, possibly as a result of long-term evolution in response to either habitat environment or life history traits. Nevertheless, the present study suggests that the difference in stress tolerance and other physiological functions, and their sensitivity to temperature, are shaped by both thermal history and habitat conditions. It provides important information for field conservation and the fisheries industry.